Structural design of al-manarah center in ramallah city - Mukhemar, Ghadeer; Jaradat, Nada; Ktaifan, Shireen (My University, 2018)
Al-Manarah Center is a multiuse faculty (commercial, offices and car parking), located in the center of Ramallah city owned by the Municipality of Ramallah. This project, which is currently under construction, consists of 15 floors of an approximate area of 25,578 m2. It consists of five basements, a ground floor, eight top floors and a roof with a total height of 53.30 m. The building stands on a cross roads of two streets with three main gates, two of them lead to the first basement floor from the main street while the third leads to the fifth basement floor. The five basements serve as parking spots and police offices, they almost have an equal area of 1900 m2. Ground, first and second floors are used as shops and police offices, with an area of 1900 m2. Finally, from the third to the roof, floors are used as shops and offices with total area of 10,242 m2. The main purpose of this building is to solve the congestion problem in the center city of Ramallah, since some of the floors of this center serve as parking spaces. Also, it is planned to relocate the police station, so it could be closer to the center of the city. Furthermore, this project has economical and commercial benefits due to the presence of offices and shops. We were interested in this project because we found it challenging to design a building with this size and floors, since it has many structural systems choices due to its long spans up to 10 m. Moreover, it contains ramps to facilitate the movement between floors. Finally, it will give us the opportunity to design curved and inclined structure to resist seismic forces. The structural model will be analyzed and designed by structural analysis and design softwares SAP, ETABS and SAFE, the results from the software will be compared to the hand calculations. In addition, AutoCAD will be used to prepare the structural drawings. ACI 318M-14 will be used as a reference for designing concrete structural elements. ASCE 7-10 and IBC2012 will be our guide in obtaining loads gravitational, wind and seismic.